Clinical features and management of equine post operative ileus: Survey of diplomates of the European Colleges of Equine Internal Medicine (ECEIM) and Veterinary Surgeons (ECVS). (12th January 2015) - Lefebvre, D.; Pirie, R. S.; Handel, I. G.; Tremaine, W. H.; Hudson, N. P. H.
Summary: Reasons for performing study: There is a need for an improved understanding of equine post operative ileus (POI), in terms of both clinical definition and optimal management. Although the pharmacological strategies that are used to treat POI continue to evolve, little is known about the supplementary strategies used to prevent and manage this condition. Objectives: To report the current strategies used to diagnose, prevent and manage POI following emergency abdominal surgeries. Study design: Cross‐sectional survey. Methods: An electronic survey invitation was sent by email to 306 European college diplomates (European Colleges of Equine Internal Medicine, ECEIM n = 120, and Veterinary Surgeons, ECVS n = 186). Results: The response rate was 33% (100 of 306). The median reported estimated incidence of POI was 10–20%. The presence of reflux on nasogastric intubation was the main criterion used to define POI. Lesions involving the small intestine were thought to be the leading risk factors for developing POI. Anti‐inflammatory drugs, antimicrobial drugs and i.v. fluids were the primary preventative strategies when managing cases at high risk for POI. Flunixin meglumine and lidocaine were the drugs most commonly used to treat horses with POI. Supplementary preventative and treatment strategies for POI included control of endotoxaemia, fluid therapy, early ambulation and judicious timing of post operative feeding. Conclusions: Appreciation of the potential risk factors associated with the development of POI appeared to have an impact on the choice of management strategies that are implemented. The majority of ECEIM and ECVS Diplomates in the survey used flunixin meglumine and lidocaine, often in combination, to treat horses with POI, which is likely to reflect the contributory role of inflammation in its pathophysiology. Various supplementary strategies were used to prevent and manage POI risk factors intraoperatively and post operatively.